Exploring the effects of the crosslink density on the physicochemical properties of collagen-based scaffolds - Luca Salvatore (Elsevier, 2021)
The optimization of collagen-based scaffolds for tissue engineering goes through the careful selection of the crosslinking method(s), which should impart the prerequisite mechanical and degradation properties without impairing the cell/tissue response. Here, we investigated the chemically effective (ρxch) and the elastically effective (ρxel) crosslink density of collagen-based scaffolds, induced by various crosslinking methods. The aim was to get a deeper insight into the influence of intramolecular and intermolecular crosslinks on several scaffold properties. Freeze-dried collagen matrices were crosslinked via a dehydrothermal treatment (DHT), and then treated with different chemical agents, including carbodiimide (EDC), glutaraldehyde (GTA), formaldehyde (FA), genipin (GP) and dimethyl suberimidate (DMS). Quantification of primary amines and stress-relaxation compressive tests were performed to evaluate ρxch and ρxel, respectively. Scaffolds were then assessed for their water uptake, thermal stability and in vitro resistance to enzymatic degradation. Interestingly, for the various crosslinking treatments ρxch was found to increase in the order DHT < DHT + GP < DHT + DMS < DHT + GTA < DHT + FA < DHT + EDC, while ρxel increased according to this slightly different trend: DHT < DHT + GP < DHT + DMS < DHT + EDC < DHT + GTA < DHT + FA. Indeed, treatment DHT + EDC induced a higher ρxch but a lower ρxel than aldehyde-based ones. This finding, together with the higher denaturation temperature (Td) of EDC-treated samples compared to others, suggested that zero-length EDC crosslinking promoted intramolecular crosslinks, along with intermolecular ones. Accordingly, the increase of Td was correlated with the increase of ρxch rather than ρxel, whereas the decrease in water uptake was consistent with the increase of ρxel, as expected. An exponential relationship between ρxel and the in vitro half-life was also determined.